Patativa do Assaré, uma hermanêutica criativa: reinvenção da religiosidade na nação semi-árida - Cobra, Cristiane Moreira (2006)
This work is the result of a bibliographic and theorical research about Patativa do Assaré´s poetry. It ascertains that the poetical discourse present in his work indicates the elaboration of contention and resistance concerning the inequality lived by his group, which uses the popular Christian religiosity as reference. The memory, orality, re-signification of concepts instituted by Church´s ortodoxy as well as the approach of pertinent themes to the members of this group are emphasized as elements of his resistent poetry. The analytical interpretation of the poems is based on the literary theory of Alfredo Bosi, the idea of identity metamorphosis developed by Ciampa as well as the analysis of Culture developed by Renato Ortiz and Clifford Geerts. Patativa makes use of the Christian Catholic religious imaginary as source of sense and meaning. He reveals to the popular culture typical forms of understanding the religiosity and the idea of Divine Providence. Furthermore he recreates, re-elaborates, re-invents and re-signifies these popular ways of attributing sense and meaning to the reality. When translated into utopia the contesting aspect present in Patativa´s poetry denotes a form of resistance. His poems manifest prayer, prophecy, value and critical conciousness of past and present, as well as hope based on popular Christian faith. The poetical discourse reveals itself as prophetic. This work contributes to the discussion about religiosity and Brazilian popular culture regarding the elaboration of a popular poetical hermeneutics. Besides, it propitiates a conception of the popular literature under models until then proclaimed as erudite. Its main conclusion is that the popular poetry of Patativa corroborates the constitution of a northeastern identity when it brings back the memory, the values, as well as the group´s self steem. Considering the identity process as a metamorphosis, which includes environmental and inner circumstances, the discourse produced by the poet is manifested as creative hermeneutics which brings sense to the world